Psychological Ownership and Organisational Fairness as Predictors of Work Motivation among Bankers in Ibadan Metropolis, Oyo State, Nigeria - AFACHUNG, Pius E; UYE, Emmanuel E; AJISAFE, Taiwo D; OLAPEGBA, Peter O. (ESUT JOURNAL OF SOCIAL SCIENCES, 2023)
Predictors of workers’ motivation have a long history in organizational development. Studies conducted to determine the predictors of work motivation have produced diverse and inconsistent results. Therefore, this study investigated psychological ownership and organizational fairness as predictors of work motivation among bankers in Ibadan metropolis. Cross-sectional survey design was adopted while purposive sampling technique was used to select three banks: First Bank of Nigeria, Access Bank, and Guaranty Trust Bank. Three instruments: Work Motivation Scale, Psychological Ownership Scale, and Organizational Fairness Scale were used to collect data from 283 bankers from the study population. Data collected were analysed using zero-ordered correlation, multiple regression and t-test of independent samples to test the three hypotheses at a p < .05 level of significance. The result indicated that psychological ownership (r =.58, p <. 05) and organizational fairness significantly correlated with work motivation among bankers in Ibadan metropolis. Also, psychological ownership and organizational fairness jointly predicted work motivation [R2 = .35, F (2.280) = 75. 48, p <.05]. Furthermore, psychological ownership (β = .53, p <.05) and organizational fairness β = .13, p <.05) independently predicted work motivation among the study population. However, gender of the bankers did not influence the level of their motivation in the organisation. The study concluded that organizational ownership and organizational fairness are strong predictors of work motivation among bankers in the study population. The study recommends that bank management should put concrete polices such as bonus sharing and contributory pension funds to boost psychological ownership and organisational fairness among bankers.